PREDICTING THE FLOW PROPERTIES OF POLYAMIDE NANOCOMPOSITES BY USING VINOGRADOV-MALKIN MODEL (JOURNAL OF ADVANCES IN PHYSICS, 2015)
This article reports the prediction of the theoretical flow curves of polyamide composites by using Vinogradov-Malkinmodel. Determination of the melt flow index of polymeric materials is the first step to study viscosity-shear raterelationship. The viscosity of the composites at different temperatures were calculated by using the Williams, Landel'a and Ferry (WLF) equation. Other important rheological characteristics were calculated by using appropriate equations. One point method is employed to correlate the changes in viscosity with temperatures. As expected, it is found that incorporation of nanoclay to polyamide 6 (PA6) significantly decreases the Melt Flow Rate of the composites and hence, increases density. Addition of stabilizer further increases density of the PA6/nanoclay composites. The simulations of viscosity curves for PA6 composites were carried out at measurement temperature, 240°C and in the range of 180°C - 350°C with shear rate of 10-1– 1031/s. It is found that addition of nanoclay and stabilizer to PA6 decreases viscosity of the composites in the order of PA6/OMMT > PA6 > PA6/I1098 > PA6/OMMT/I1098 > PA6/MMT/I1098 > PA6/MMT. At higher shear rates, viscosity decreases in the same sequence as low shear rates. At further higher shear rates (> 1000 1/s), fillerparticles are arranged in the flow direction thus exerting no significant effect on viscosity of composites both with and without the stabilizer. During injection moulding in the shear rate ranging from 101 – 104 1/s at 240°C temperature, it is evident that viscosity decreases drastically with increase in shear rate